Analisis Kelayakan Pada Usahatani Buah Naga di Desa Sumbersari Kecamatan Sumbersari Kabupaten Jember - Rohmad Fajar Hidayatullah (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
The feasibility analysis on the dragon fruit farming in Sumbersari Village, Sumbersari Subdistrict, Jember Regency was conducted to look at the financial, technical, market and management aspects. The method of determining the location is done using purposive methods by considering the suitability of the object under study. The financial feasibility aspect uses several analysis tools namely Gross B / c ratio, Net B / C Ratio, payback period, Net Present Value, Internal Rate of Return, and sensitivity analysis. The results showed a NPV value of Rp 1,213,493,768, Net B / C of 6.46, Gross B / C of 3.44, IRR of 73%, PR of 14.64, PP of 2 years 8 months 15 days, and sensitivity analysis shows if the increase in prices of all variables by 5% and 10% still shows positive or reasonable results for all investment criteria.